1993
DOI: 10.1111/j.1365-2265.1993.tb02376.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of insulin insensitivity to menstrual pattern in women with hyperandrogenism and polycystic ovaries

Abstract: Insulin insensitivity in polycystic ovary syndrome occurs when there is oligo/amenorrhoea but not when the menstrual cycle is regular. This is consistent with PCO and insulin insensitivity being separate abnormalities which when combined are associated with anovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
2
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(129 citation statements)
references
References 20 publications
5
115
2
7
Order By: Relevance
“…The group of women with one or two class III alleles had significantly higher fasting insulin levels and higher mean body mass index than women with I/I genotype. This is in agreement with the observation that hyperinsulinaemia is a more prominent feature in women with polycystic ovaries who have anovulatory menses than in equally hyperandrogenaemic subjects with regular menses (35). It has also been observed that the homozygous genotype III/III is more frequent among women with polycystic ovaries and symptoms than among women with polycystic ovaries without symptoms (34).…”
Section: The Insulin Genesupporting
confidence: 80%
“…The group of women with one or two class III alleles had significantly higher fasting insulin levels and higher mean body mass index than women with I/I genotype. This is in agreement with the observation that hyperinsulinaemia is a more prominent feature in women with polycystic ovaries who have anovulatory menses than in equally hyperandrogenaemic subjects with regular menses (35). It has also been observed that the homozygous genotype III/III is more frequent among women with polycystic ovaries and symptoms than among women with polycystic ovaries without symptoms (34).…”
Section: The Insulin Genesupporting
confidence: 80%
“…secondary amenorrhea or with regular menstrual cycles did not differ in markers of IR from Group D. Two previous smaller studies (nZ72 and nZ418 respectively) reported that patients with PCOS and oligomenorrhea or amenorrhea had more severe IR than patients with PCOS and regular cycles (10,11). However, the latter studies did not differentiate between patients with oligomenorrhea and amenorrhea (10,11).…”
Section: Tablementioning
confidence: 48%
“…Therefore, menstrual cycle pattern might serve as a marker of IR in patients with PCOS, as IR can induce oligo-or anovulation and thus menstrual cycle irregularity by exacerbating hyperandrogenemia and by disrupting follicular growth (2). Nevertheless, very few small studies evaluated the association between menstruation abnormalities and the endocrine and metabolic characteristics in PCOS (10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, it seems that insulin resistance in PCOS is disproportionate to the degree of obesity; it should, however, be considered that it is invariably present in all obese women (39). Interestingly, it has been reported that ovulatory women with PCOS are less insulin-resistant than anovulatory PCOS ones (40). Obesity is known to increase androgen and insulin levels and, consequently, it is suggested that it may increase PCOS prevalence and exacerbate the clinical features of PCOS (41).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%